2020
DOI: 10.1080/21681805.2020.1821766
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of autoimmune disorders among bladder pain syndrome patients’ relatives

Abstract: Purpose: Possible genetic background and autoimmune etiology of Bladder Pain Syndrome (BPS, formerly Interstitial Cystitis, IC) has been suggested. We studied whether familial clustering of BPS, other autoimmune diseases or fibromyalgia exist among BPS patients' genetically close relatives; possibly reflecting some common predisposing genetic background of these diseases. Materials and methods: Altogether 420 first-or second-degree relatives of 94 BPS patients fulfilling the NIDDK criteria were asked to fill i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…15 Therefore, our approach using blood samples may reflect the basal pathological state of IC/BPS, which is a chronic disease that is relatively stable compared to acute conditions. As IC/BPS is often associated with immune-related diseases, such as irritable bowel syndrome, fibromyalgia, and inflammatory bowel disease, 48 the pathology of IC/BPS may be systemic rather than localized in the bladder. Therefore, it is reasonable to search for biomarkers in the blood.…”
Section: Metabolitesmentioning
confidence: 99%
“…15 Therefore, our approach using blood samples may reflect the basal pathological state of IC/BPS, which is a chronic disease that is relatively stable compared to acute conditions. As IC/BPS is often associated with immune-related diseases, such as irritable bowel syndrome, fibromyalgia, and inflammatory bowel disease, 48 the pathology of IC/BPS may be systemic rather than localized in the bladder. Therefore, it is reasonable to search for biomarkers in the blood.…”
Section: Metabolitesmentioning
confidence: 99%
“…Additionally, BPS/IC seems to occur in many cases together with other chronic comorbidities such as allergies (e.g. atopic dermatitis) [3], autoimmune disorders (e.g. Hashimotos's thyroiditis, ankylosing spondylitis, Sj€ ogren's syndrome, lupus erythematosus and rheumatoid arthritis) [4,5], chronic inflammatory disorders (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hashimotos's thyroiditis, ankylosing spondylitis, Sj€ ogren's syndrome, lupus erythematosus and rheumatoid arthritis) [4,5], chronic inflammatory disorders (e.g. ulcerative colitis and psoriasis) [3,4] and chronic pain and functional conditions [e.g. endometriosis, irritable bowel syndrome (IBS), fibromyalgia and chronic fatigue] [3,4,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported on autoantibodies in patients with IC/BPS ( 3 5 ). Kujala et al proposed a possible link between ADs and IC/BPS in patients with certain immunological factors or genetic predispositions ( 6 ). Numerous studies on autoantibodies against nuclear or bladder epithelium antigens in patients with IC/BPS appear in the literature ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%